2017
DOI: 10.3892/ol.2017.7331
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-26b-5p regulates cell proliferation, invasion and metastasis in human intrahepatic cholangiocarcinoma by targeting S100A7

Abstract: Abstract. The present study aimed to investigate the effects of microRNA expression in intrahepatic cholangiocarcinoma (ICC). It was identified that the expression of microRNA-26b-5p (miR-26b-5p) was downregulated in ICC tissues compared with matched adjacent non-tumor tissues. Furthermore, miR-26b-5p expression was downregulated in metastatic ICC tumor tissues and invasive ICC cell line subpopulations compared with non-metastatic tumor tissue and the parental ICC cells. In vitro studies demonstrated that tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…The expression of S100A7 could be downregulated by miR-26b-5p, leading to decreased proliferation, migration, and invasion of intrahepatic cholangiocarcinoma in vitro [241]. Similar effects were observed for miR-24, a miRNA targeting S100A8, which inhibited proliferation and invasion of laryngeal carcinoma cells [242].…”
Section: Micro Rna (Mirna) Mimicssupporting
confidence: 56%
See 1 more Smart Citation
“…The expression of S100A7 could be downregulated by miR-26b-5p, leading to decreased proliferation, migration, and invasion of intrahepatic cholangiocarcinoma in vitro [241]. Similar effects were observed for miR-24, a miRNA targeting S100A8, which inhibited proliferation and invasion of laryngeal carcinoma cells [242].…”
Section: Micro Rna (Mirna) Mimicssupporting
confidence: 56%
“…Pre-clinical [239] miR-193a S100A6 S100A6 silencing results in suppression of proliferation, invasion, migration, and angiogenesis within lung cancer models Pre-clinical [240] miR-26b-5p S100A7 S100A7 silencing inhibits proliferation, invasion, and migration of intrahepatic cholangiocarcinoma cells Pre-clinical [241] miR-24 S100A8…”
Section: S100a4 Silencing Results In Inhibition Of Invasion and Migramentioning
confidence: 99%
“…Invasion and metastasis are important biological chara-cteristics of malignant tumors including MCL. Tumor growth, invasion and metastasis involve a complex multistep process, including the division and proliferation of tumor cells, the degradation of the extracellular matrix, cell escape through the basement membrane, migration into the blood circulation system, tumor cell growth at secondary sites and a series of activities, at the same time accompanied by the formation of new blood vessels ( 4 ). Studies have shown that MMP9, a member of the matrix metalloproteinase (MMP) family is highly expressed in various tumors and plays a major role in the growth, metastasis and angiogenesis of primary and secondary tumors ( 5 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Specific microRNA segments have been identified to play different roles in the regulations of much pathology [98]. In a published study, the analysis of 80 different liver samples, half of which included tissues with intrahepatic CCA, identified that downregulated microRNA-26b-5p was associated with intrahepatic CCA diagnosis [99]. Additionally, downregulated microRNA-26b-5p correlated with increased invasive capacity of CCA.…”
Section: Introductionmentioning
confidence: 99%
“…S100 calcium-binding protein A7, which is implicated in the progression of CCA, was found to be a downregulated by microRNA-26b-5p. This is the proposed target that causes the effect of decreased invasion of CCA [99]. MicroRNA-34a is another miRNA that has been found to play a role in the circadian rhythms of humans [100].…”
Section: Introductionmentioning
confidence: 99%